A STUDY ON TEACHING-LEARNING PROCESS OF ENGLISH READING OF THE FIFTH YEAR STUDENTS OF SDN 1 WANADADI: A NATURALISTIC STUDY - SARI, ACHRIYANI KELANA (2007)
This research is conducted to know the process of teaching English reading adopting the Natural Study. It is aimed at observing the teaching of English reading using natural study at SDN1 Wanadadi. The writer takes the English teacher and students of class 5 as the subject of the study. which is focused on: type of syllabus, type of teaching learning activities, and roles of the student and teacher in teaching learning process. The primary data are mainly taken from observation. The secondary data are obtained from teaching material and information about teaching-learning process of English teacher. In collecting the data, the writer uses teaching observation. Meanwhile, the data are analyzed by using descriptive qualitative method. After analyzing the observation findings, the writer draws some conclusion about the process of teaching and learning English reading of the fifth year student's of SDN1 Wanadadi, which focused on; (1) Type of syllabus is the point where the teacher make syllabus to plan the material. (2) Type of teaching learning activities, is descriptions: reading aloud, dialogue, discussion, and game. (3) Role of the students and the teacher in teaching learning process. Role of the students they are the subject not the object and a negotiator. The role of teacher in teaching learning process is teacher as a manager, a facilitator, a counselor, an instructor, and an evaluator. The evaluation of teaching learning process of English reading uses the oral test.